Components, drivers and temporal dynamics of ecosystem respiration in a Mediterranean pine forest. (September 2015) - Matteucci, Marco; Gruening, Carsten; Goded Ballarin, Ignacio; Seufert, Guenther; Cescatti, Alessandro
Abstract: To investigate the climate impacts on the different components of ecosystem respiration, we combined soil efflux data from a tree-girdling experiment with eddy covariance CO2 fluxes in a Mediterranean maritime pine ( Pinus pinaster ) forest in Central Italy. 73 trees were stem girdled to stop the flux of photosynthates from the canopy to the roots, and weekly soil respiration surveys were carried out for one year. Heterotrophic respiration ( R H ) was estimated from the soil CO2 flux measured in girdled plots, and rhizosphere respiration ( R Ab ) was calculated as the difference between respiration from controls ( R S ) and girdled plots ( R H ). Results show that the R S dynamics were clearly driven by R H (average R H / R S ratio 0.74). R H predictably responded to environmental variables, being predominantly controlled by soil water availability during the hot and dry growing season (May–October) and by soil temperature during the wetter and colder months (November–March). High R S and R H peaks were recorded after rain pulses greater than 10 mm on dry soil, indicating that large soil carbon emissions were driven by the rapid microbial oxidation of labile carbon compounds. We also observed a time-lag of one week between water pulses and R Ab peaks, which might be due to the delay in the translocation of recently assimilated photosynthates from the canopy to the root system. At the ecosystem scale, total autotrophic respiration ( R At, i.e. the sum of carbon respired by the rhizosphere and aboveground biomass) amounted to 60% of ecosystem respiration. R At was predominantly controlled by photosynthesis, and showed high temperature sensitivity ( Q 10 ) only during the wet periods. Despite the fact that the study coincided with an anomalous dry year and results might therefore not represent a general pattern, these data highlight the complex climatic control of the respiratory processes responsible for ecosystem CO2 emissions. Highlights: Combining eddy covariance with tree girdling to partition ecosystem respiration. Autotrophic respiration is prevalently controlled by the dynamic of photosynthesis. Soil water content and temperature drive heterotrophic and total soil respiration. Quick and large soil CO2 pulses after rainfall are due to heterotrophic respiration. The response of rhizosphere respiration to a water pulse is time-lagged.